Exemplar Hospital Initiation Trial to Enhance Treatment Engagement (EXHIT ENTRE): protocol for CTN-0098 an open-label randomized comparative effectiveness trial of extended-release buprenorphine versus treatment as usual on post-hospital treatment engagement for hospitalized patients with opioid use disorder - Gavin Bart; Kelly S. Barth; Paulette Baukol; Eva Enns; Udi E. Ghitza; Jacklyn Harris; Eve Jelstrom; Jane M. Liebschutz; Kara M. Magane; Delia Voronca; Zoe M. Weinstein; P. Todd Korthuis (Addiction Science & Clinical Practice)
Abstract Background Hospitalizations involving opioid use disorder (OUD) are increasing. Addiction consultation services (ACS) initiate medications for opioid use disorder (MOUD) in hospital settings and arrange post-hospital follow-up for ongoing MOUD care. Engagement in MOUD following hospital discharge is hampered by challenges in timely access to MOUD. This protocol describes an open-label randomized comparative effectiveness trial comparing ACS treatment as usual (TAU) to a single injection of a 28-day formulation extended-release buprenorphine (XR-BUP) on MOUD engagement 34-days following hospital discharge. Methods Six U.S. hospitals with ACS capable of prescribing all MOUD (i.e., methadone, buprenorphine, and extended-release naltrexone) recruit and randomize hospitalized patients with OUD who have not been on MOUD in the fourteen days prior to hospitalization. TAU may consist of any MOUD other than XR-BUP. Participants randomized to XR-BUP may receive any MOUD throughout their hospital stay and receive a 28-day XR-BUP injection within 72-hours of anticipated hospital discharge. There is no intervention beyond hospital stay. Participants are followed 34-, 90-, and 180-days following hospital discharge. The primary outcome is engagement in any MOUD 34-days following hospital discharge, which we hypothesize will be greater in the XR-BUP group. Randomizing 342 participants (171 per arm) provides 90% power to detect difference in the primary outcome between groups with an odds ratio of 2.1. Safety, secondary, and exploratory outcomes include: adverse events, MOUD engagement on days 90 and 180, opioid positive urine drug tests, self-reported drug use, hospital readmissions and emergency department visits, use of non-opioid drugs, fatal and non-fatal opioid overdose, all-cause mortality, quality of life, and cost-effectiveness. Data are analyzed by intention-to-treat, with pre-planned per-protocol and other secondary analyses that examine gender as an effect modifier, differences between groups, and impact of missingness. Discussion Engagement in MOUD care following hospitalization in individuals with OUD is low. This randomized comparative effectiveness trial can inform hospital ACS in medication selection to improve MOUD engagement 34-days following hospital discharge. Trial registration NCT04345718.